2008
DOI: 10.1021/jp7110956
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Properties of PtBi and PtPb Intermetallic Line Compounds via DFT: CO and H Adsorption

Abstract: Pt intermetallic line compounds, such as with Pb and Bi, have been observed to improve dramatically the anode carbon monoxide (CO) tolerance of fuel cells for oxidation of small organic molecules. We have used density functional theory to study the CO and H adsorption on different surfaces of these line compounds. Among different surface orientations of PtPb and PtBi, we find (100)B and (110) have much lower cleavage energies and CO adsorption energies than (100)A and (001) and also much lower CO adsorption en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…The reduction in adsorption energies is expected from our earlier study of H and CO adsorption on PtPb and PtBi surfaces 47 having the same NiAs structure, because the Pt dband center on (110) is pushed toward lower energy and further away from the Fermi level due to the charge transfer from the p-metals. From PDOS (Figure 8c), this is clearly shown by furfural on PtSn (110) retaining the molecular HOMO−1 (−3.5 eV), HOMO (−2.5 eV), LUMO (0.5 eV) and LUMO+1 (3.0 eV) states with part of the broadened LUMO-derived band shifted below the Fermi level and filled by charge transfer from Sn.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The reduction in adsorption energies is expected from our earlier study of H and CO adsorption on PtPb and PtBi surfaces 47 having the same NiAs structure, because the Pt dband center on (110) is pushed toward lower energy and further away from the Fermi level due to the charge transfer from the p-metals. From PDOS (Figure 8c), this is clearly shown by furfural on PtSn (110) retaining the molecular HOMO−1 (−3.5 eV), HOMO (−2.5 eV), LUMO (0.5 eV) and LUMO+1 (3.0 eV) states with part of the broadened LUMO-derived band shifted below the Fermi level and filled by charge transfer from Sn.…”
Section: Resultsmentioning
confidence: 55%
“…This behavior agrees with our earlier study on PtPb and PtBi compounds in the same NiAs structure. 47 For the adsorption of furfural, the most stable configurations on Pt(111) and PtSn(110) are shown in Figure 8a and b, respectively, with their corresponding projected density of states (PDOS) shown in (c). On Pt(111), the most preferred configuration is flat with the two CC bonds in the furan ring and the CO bond sitting along three different Pt−Pt bridge sites, agreeing with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the ordering temperatures are so low (below the room temperature), it is very hard to obtain these ordered phases, while ordered structures are not experimentally observed for the Pt–Ru system, even if they are theoretically predicted . Finally, post‐transition metals do not form random alloy, but only form ordered intermetallics, such as PtPb, PtBi, and PtBi 2 …”
Section: Crystal Structure and Surface Composition Of Pt‐based Binarymentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] Fourier transform infrared spectroscopy (FT-IR) and differential electrochemical mass spectroscopy (DEMS) studies have shown that formic acid oxidation on PtPb, in contrast to Pt, occurs via a non-CO ads reaction pathway. [24][25][26][27][28] Theoretical work has been performed to assess the nature of CO interactions with various surfaces of the equilibrium Pt-Pb 30,31 and Pt 3 Pb 30 phases. The PtPb intermetallic phase has also been shown to be particularly active for glucose oxidation.…”
mentioning
confidence: 99%